2019
DOI: 10.2147/ott.s236659
|View full text |Cite
|
Sign up to set email alerts
|

<p>Akt/mTOR-Mediated Autophagy Confers Resistance To BET Inhibitor JQ1 In Ovarian Cancer [Corrigendum]</p>

Abstract: The authors of this paper have advised that when they rechecked their data and figures, they found one mistake in Figure 1C on page 8065. Figure 1C reflects the effects of different concentrations of JQ1 on the apoptosis level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Interestingly, interferon signaling which is significantly attenuated in our JQ1-treated tumors is highly correlated with sensitivity to JQ1, suggesting a possible higher dependence of the sensitive clones on these pathways. Conversely resistance is associated with higher levels of unfolded protein response and mTOR signaling consistent with a known role of mTOR-mediated autophagy in resistance to JQ1 (Luan et al, 2019), and cytotoxic synergy between PI3K/mTOR inhibitors and BET inhibitors (Lee et al, 2015; Stratikopoulos et al, 2015).…”
Section: Resultsmentioning
confidence: 58%
“…Interestingly, interferon signaling which is significantly attenuated in our JQ1-treated tumors is highly correlated with sensitivity to JQ1, suggesting a possible higher dependence of the sensitive clones on these pathways. Conversely resistance is associated with higher levels of unfolded protein response and mTOR signaling consistent with a known role of mTOR-mediated autophagy in resistance to JQ1 (Luan et al, 2019), and cytotoxic synergy between PI3K/mTOR inhibitors and BET inhibitors (Lee et al, 2015; Stratikopoulos et al, 2015).…”
Section: Resultsmentioning
confidence: 58%
“…This is because autophagy has two opposite roles in tumour cells: cytoprotective and cytotoxic 67 . In ovarian cancer and acute myeloid leukaemia in humans, JQ1‐induced autophagy had a cytoprotective role and an autophagy inhibitor enhanced the anti‐tumour effect of JQ1 68,69 . Conversely, in human bladder cancer cell lines, the proliferation suppression capacity of JQ1 was attenuated by autophagy inhibitors, which suggested that JQ1‐induced autophagy had a cytotoxic role 23 .…”
Section: Discussionmentioning
confidence: 99%
“…67 In ovarian cancer and acute myeloid leukaemia in humans, JQ1-induced autophagy had a cytoprotective role and an autophagy inhibitor enhanced the anti-tumour effect of JQ1. 68,69 Conversely, in human bladder cancer cell lines, the proliferation suppression capacity of JQ1 was attenuated by autophagy inhibitors, which suggested that JQ1-induced autophagy had a cytotoxic role. 23 Further experiments are needed to elucidate which roles JQ1-induced autophagy has in HSA.…”
Section: Discussionmentioning
confidence: 99%
“…For TNBC, the cells can rapidly develop resistance due to various mechanisms, including changes in signaling pathways involving ZNF33A upregulation, deletion of SNF/SWI complex components as well as ubiquitination-related genes such as SPOP, UBE2M, CUL3 and USP14 ( 147 , 148 ). In ovarian cancer cell lines, autophagy (shown by increased expression of ATG5 and Beclin1) induced by inactivation of Akt (Ser473)/mTOR (Ser2448) pathway, is linked with resistance to BETi possibly as a way to bypass BET inhibition ( 149 ). Thus, it is essential to note that resistance to JQ1 has distinct mechanisms depending on cancer types; however, increase in Myc expression has been pinpointed as common cause of resistance to BETi ( 147 , 150 , 151 ).…”
Section: Resistance To Bet Inhibitionmentioning
confidence: 99%